Endoscopic removal of foreign bodies from the upper aerodigestive tract: a retrospective study from a tertiary care hospital - Vellamparambil, Sreeja Raj; Menon, Arjun Gopinath; Rajagopalan Vinayakumar, Ariyamparambil (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Foreign bodies (FB) in the upper aero-digestive tract pose major challenges to the otorhinolaryngologist in both diagnosis and management. Aspirated and ingested foreign bodies are often emergencies, leading to inadequate study, poor preparation and improper attempts at removal. A retrospective analysis was done on cases which were managed for the upper aero-digestive tract FBs in a tertiary care hospital in South India and the result is presented in this article. Methods: Retrospective study was done on 100 patients diagnosed as cases of foreign body in upper aerodigestive tract on the basis of detailed history, clinical examination and radiological investigation. They underwent per oral endoscopy under general anaesthesia for retrieval of foreign body. Results: Age group more prone for foreign body ingestion or aspiration was <10 years and >50 years. Most common site of impaction in oesophagus is cricopharynx and in airway is right bronchus. Most common type of FB is chicken bone. Most common symptom in FB ingestion is FB sensation and in case of FB aspiration it is cough. Most (82%) of the FBs were radio opaque. Conclusions: Accurate history and clinical examination were the keystones in diagnosis and prevention of complications of FB lodgement in aerodigestive tract. Negative history and or normal imaging do not rule out a foreign body.